2016
DOI: 10.3892/mmr.2016.5967
|View full text |Cite
|
Sign up to set email alerts
|

Calcineurin/nuclear factor-κB signaling mediates isoflurane-induced hippocampal neuroinflammation and subsequent cognitive impairment in aged rats

Abstract: It is known that inhaled anesthetics induce neuroinflammation and facilitate postoperative cognitive dysfunction (POCD) in aged individuals; however, the mechanisms by which they mediate these effects remain elusive. Inhalation of the isoflurane anesthetic leads to opening of the mitochondrial permeability transition pore and loss of mitochondrial membrane potential. Therefore, mitochondrial retrograde signaling, which is an adaptive mechanism that facilitates the transmission of signals from dysfunctional mit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 43 publications
0
34
0
Order By: Relevance
“…The commonly used inhalation anesthetic isoflurane has been shown to induce activation of nuclear factor (NF)-κB, a master regulator of inflammation ( 8 ), increase TNF-α, IL-6 and IL-1β in the aged brain ( 9 ), and is associated with increased risk of cognitive dysfunction in the elderly. Hypoxia-inducible factor 1α (HIF-1α) is upregulated by factors such as angiotensinII ( 10 ) and carbachol ( 11 ), even though HIF-1α plays a major role in the maintenance of oxygen homeostasis and cellular adaptation ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…The commonly used inhalation anesthetic isoflurane has been shown to induce activation of nuclear factor (NF)-κB, a master regulator of inflammation ( 8 ), increase TNF-α, IL-6 and IL-1β in the aged brain ( 9 ), and is associated with increased risk of cognitive dysfunction in the elderly. Hypoxia-inducible factor 1α (HIF-1α) is upregulated by factors such as angiotensinII ( 10 ) and carbachol ( 11 ), even though HIF-1α plays a major role in the maintenance of oxygen homeostasis and cellular adaptation ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…; Li et al . ). Thus, next, we analysed the activities of CaMKII, CaMKIV and NFAT in damaged muscle.…”
Section: Resultsmentioning
confidence: 97%
“…Some examples include upregulation of T-cell associated markers Ly6a and Ctla2a, upregulation of adhesion markers Pecam1 and CD93, and downregulation of Nfkbia, the protein product of which inhibits NF-κB. Indeed, activation of NF-κB has been proposed as a mechanism by which volatile anesthetics elicit neuroinflammation [50,51]. Several rodent studies have demonstrated volatile anesthetics can also acutely induce expression of IL-6, IL-1β, and activated caspase-3 [52][53][54][55].…”
Section: Discussionmentioning
confidence: 99%